Paternity Analysis of Tea (Camellia sinensis L. Kuntz) Hybrids Using Isozyme Marker - Titin Setyorini; T. Taryono; S. Suyadi; Sapto Indrioko (Universitas Gadjah Mada, 2012)
Tea plant has been categorized as self-incompatible crop. This is the reason behind the high genetic diversity. Natural pollination is possible to occur and the male parent is usually unknown, therefore, there is a need of method to identify male parent of hybrids through paternity analysis. Isozyme markers have been successfully used for paternity analysis due to their co-dominant polymorphism. This research aimed to predict male parents of hybrids by figuring out the mating system through isozyme banding patterns. In this experiment, seven enzyme systems were evaluated, of which only two of the enzyme systems i.e. esterase and shikimate dehydrogenase showing clear band pattern of Est-1, Est-2, and Shd-1 loci. The mating system of tea could be categorized as a mixed mating model, with high estimated out-crossing rate of 98.6 %. The pollen contributors were not always originated from the vicinity of the female parents.Key words: isozyme markers, paternity analysis, tea